2010
DOI: 10.1007/s11661-009-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of a Laser-Processed Zr-Based Bulk Metallic Glass

Abstract: Laser processing is a precision manufacturing technique capable of producing materials with highly nonequilibrium microstructures. Due to the localized heat input and high cooling rate inherent to the process, this technology is attractive for the production of metallic glasses. In the present work, we use a laser deposition process to deposit a Zr-based metallic glass forming powder on both amorphous and crystalline substrates of the same nominal composition. Amorphous melt zones are observed surrounded by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…The narrowing of the amorphous regions in the graded specimen can be explained by the general effect of k on an alloy's ability to vitrify. Sun and Flores carried out laser deposition experiments with a Zr-based BMG powder on amorphous substrates and reported a dependence of glass formation on k. [31,32] It was specifically observed that decreasing k below a threshold value by fixing the laser power and increasing the travel speed nearly eliminated crystallinity in the heat-affected zone. Chen et al performed laser surface melting experiments with Cu 60 Zr 30 Ti 10 substrates and reported the same effect of travel speed on the ability of the local melt pool to fully vitrify.…”
Section: Discussionmentioning
confidence: 99%
“…The narrowing of the amorphous regions in the graded specimen can be explained by the general effect of k on an alloy's ability to vitrify. Sun and Flores carried out laser deposition experiments with a Zr-based BMG powder on amorphous substrates and reported a dependence of glass formation on k. [31,32] It was specifically observed that decreasing k below a threshold value by fixing the laser power and increasing the travel speed nearly eliminated crystallinity in the heat-affected zone. Chen et al performed laser surface melting experiments with Cu 60 Zr 30 Ti 10 substrates and reported the same effect of travel speed on the ability of the local melt pool to fully vitrify.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that spherulite growth is initiated on pre-existing nuclei frozen into the metallic glass. The results appear to be insensitive to the heating rate, with heating rates as high as 10 3 K s −1 being found not to inhibit spherulite crystallisation [25].…”
Section: Introductionmentioning
confidence: 86%
“…Bulk metallic glasses (BMGs) with both glassy-state structure and metallic-bonding character show a series of intriguing mechanical, physical, and chemical properties, having wide range functional and structural applications. [8][9][10][11][12] Due to rapid heating and cooling, lasers have been widely used to welding, cutting, cladding, alloying, glazing, annealing, melting, or ablating the small-scaled amorphous alloys such as ribbons, films, and wires, [13][14][15][16][17] very recently extending to BMGs. 18,19 Through laser-processing, microstructures, 15-17 magnetic properties, 14 forming ability, 20 and mechanical properties 19 of this kind of glassy alloys can be significantly improved, whereas only few works have focused on the surface patterns.…”
mentioning
confidence: 99%